2021
DOI: 10.3390/ma14164495
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic to Isotropic Transition in Monolayer Group-IV Tellurides

Abstract: Monolayer group-IV tellurides with phosphorene-derived structures are attracting increasing research interest because of their unique properties. Here, we systematically studied the quasiparticle electronic and optical properties of two-dimensional group-IV tellurides (SiTe, GeTe, SnTe, PbTe) using the GW and Bethe–Salpeter equation method. The calculations revealed that all group-IV tellurides are indirect bandgap semiconductors except for monolayer PbTe with a direct gap of 1.742 eV, while all of them are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
0
6
1
Order By: Relevance
“…We found no evidence for the formation of any phases of SiTe and Si 2 Te 3 reported earlier from theoretical predictions. 5,[10][11][12]14 The F-centered clathrate Te 7+x Si 20−x (cF) was identified for the compositional mix of Si 38 /Te 16 , where it formed simultaneously with the Te 8 @(Si 38 Te 8 )-type clathrate after the hexagonal phase disappeared (Figure S2). At higher temperatures, the Te 8 @(Si 38 Te 8 )-type clathrate is favored and is retained on cooling.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no evidence for the formation of any phases of SiTe and Si 2 Te 3 reported earlier from theoretical predictions. 5,[10][11][12]14 The F-centered clathrate Te 7+x Si 20−x (cF) was identified for the compositional mix of Si 38 /Te 16 , where it formed simultaneously with the Te 8 @(Si 38 Te 8 )-type clathrate after the hexagonal phase disappeared (Figure S2). At higher temperatures, the Te 8 @(Si 38 Te 8 )-type clathrate is favored and is retained on cooling.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…11 Altogether, the bulk IV−VI compounds have structures derived from a black phosphorene, which is a distorted variant of the NaCl structure. 12 Quantum-chemical calculations suggested a plausible synthetic approach to silicon monotelluride since silicon can be incorporated into the crystal structure of Si 2 Te 3 to yield SiTe at pressures of about 7 GPa. 5 Several candidates for the hypothetical high-pressure phase of SiTe were proposed and their formation enthalpies were obtained from density functional theory (DFT) calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…All these GeTe phases are dynamically stable according to the literature, e.g., Reference [18] for cubic and rhombohedral GeTe, Reference [19] for puckered GeTe, and Reference [20] for buckled GeTe. There have also been earlier DFT calculations for the electronic band structures of GeTe monolayers in the puckered lattice [19,[21][22][23] and buckled lattice [23,24], but the results seem to be inconsistent with a recent experiment [25]. In Reference [25], Zhang et al only observed buckled GeTe thin films in argon and oxygen environments with band gaps of about 1.89-2.08 eV, while References [23,24] obtained band gaps of about 2.35 eV.…”
Section: Introductionmentioning
confidence: 90%
“…However, since we are interested in the qualitative comparison between optical spectra of the bulk and monolayer GeTe to judge their possible absorption performance, it is sufficient to consider the independent particle and dipole approximation. For GeTe, the relative absorption coefficients calculated using this approach should not be much different from that calculated with the GW method [22].…”
Section: Optical Coefficientsmentioning
confidence: 96%
See 1 more Smart Citation